Constrained Agency Theory and Leadership: A New Perspective to Understand How Female Police Officers Overcome the Structural and Social Impediments to Promotion. (July 2018) - Morabito, Melissa S.; Shelley, Tara O'Connor
Substantial research has examined both the barriers preventing women from entering and flourishing in policing and the coping mechanisms used to adapt to the gendered institution of policing. However, there is scant research that examines the mechanisms by which some women successfully navigate the police bureaucracy. Drawing from in-depth, semi-structured interviews of 47 female officers from 30 law enforcement agencies across seven states, we apply Constrained Agency Theory as a means to identify and understand how women capitalize on conditions and opportunities to advance and/or gain promotion in gendered organizations. The purpose of our research is to explore the efficacy of this theoretical framework for the study of women in policing. Results suggest that Constrained Agency Theory offers a promising way of understanding how female officers experience and utilize opportunities and conditions for advancement across a variety of agencies, generations, and organizational cultures.